Effective connectivity of the left-ventral occipito-temporal cortex during visual word processing: Direct causal evidence from TMS-EEG co-registration. - Planton, Samuel; Wang, Shuai; Bolger, Deirdre; Bonnard, Mireille; Pattamadilok, Chotiga (Cortex: A Journal Devoted to the Study of the Nervous System & Behavior, 2022)
As an interface between the visual and language system, the left ventral occipito-temporal cortex (left-vOT) plays a key role in reading. This functional role is supported by anatomical and functional connections between the area and other brain regions within and outside the language network. Nevertheless, only a few studies have investigated how the functional state of this area, which is dependent upon the nature of the task demand and the stimulus being processed, could influence the activity of the connected brain regions. In the present combined TMS-EEG study, we studied the left-vOT effective connectivity by adopting a direct, causal intervention approach. Using TMS, we probed left-vOT activation in different processing contexts and measured the neural propagation of activity from this area to other brain regions. A comparison of neural propagation measured during low-level visual detection of language versus non-language stimuli showed that processing language stimuli reduced neural propagation from the left-vOT to the right occipital cortex. Additionally, compared to the low-level visual detection of language stimuli, performing semantic judgments on the same stimuli further reduced neural propagation to the posterior part of the corpus callosum, right superior parietal lobule and the right anterior temporal lobe. This reduction of cross-hemispheric neural propagation was accompanied by an increase in the collaboration between areas within the left-hemisphere language network. Together, this first evidence from a direct causal intervention approach suggests that processing language stimuli and performing a high-level language task reduce effective connectivity from the left-vOT to the right hemisphere, and may contribute to the left-hemisphere lateralization typically observed during language processing.